Torture: an experience that limits human dignity - Quezada Zevallos, Jenny (2003)
Torture constitute one of the most catastrophic experiences that can lead to a post-traumatic stress disorder. Observation and analysis of people who experienced torture have allowed to know a variety of important aspect of understanding this mental disorder and considering this mental disorder and considering therapeutic intervention on patients as well as on their relatives.